Risk Factors Affecting Stunting of Toddlers in Murtajih Village, Pamekasan District: Faktor Risiko yang Mempengaruhi Kejadian Stunting pada Balita di Desa Murtajih, Kabupaten Pamekasan - Arifah Annisa Fikri; I Nengah Tanu Komalyna (Universitas Airlangga, 2023)
The incidence of stunting in toddlers is still high which is caused by inadequate nutritional intake in the long term. The purposed of this study is to analyze the risk factors for stunting in children under five. This research was conducted from November 24 - December 7, 2021, in Murtajih Village, Pamekasan Regency. This research design uses the case control method. Respondents as the case group in this study were mothers with toddlers aged 12 – 59 months with nutritional status in the stunting category, and respondents as control groups were mothers with toddlers of the same age with normal nutritional status. Data analysis used the Chi-square test and logistic regression. The results of the analysis showed that the risk factors for stunting in children under five were the respondents consuming the amount of blood-added tablets during pregnancy that did not meet the standard (OR= 11; 95% CI= 1.998–60.572), birth length (OR= 4; 95% CI= 0.983–16.271), breastfeeding status (OR = 7.364; 95% CI= 1.337 – 40.548), basic immunization status (OR= 6; 95% CI= 1.082–33.274), history of diarrheal disease (OR= 0.074; 95% CI = 0.013 – 0.411), and a history of ARI (OR= 0.095; 95% CI= 0.021 – 0.440). It can be concluded that the consumption of Iron and Folic Acid (IFA) tablet does not match the standard and is the most dominant risk factor for stunting in children under five. Meanwhile, toddlers who do not have a history of diarrhea and ARI can prevent the risk of stunting in toddlers.